The Principal's Leadership Role In Improving School Quality - Gule, Azizah; Alawiyah, Tuti; Nainggolan, Andrean Syahputra; Elfrianto, Elfrianto (Indonesian Journal Education, 2024)
This research aims to evaluate the quality of education, the role of the principal, the principal's leadership style, and the principal's leadership strategies. The research method used is qualitative with a case study typology. Primary and secondary data are used as data sources. The data collection techniques used were observation, interviews and documentation. The results of the research show that the quality of education meets 8 National Education standards, the role of education meets 8 (eight) National Education standards, the role of the principal in supporting improving the quality of education, and the leadership style used by the principal, democratic leadership style, the Principal's strategy in improving quality Education, the quality of education related to human resource development programs, curriculum, teacher professionalism, student affairs, physical facilities and infrastructure, community relations and fund (financial) management.